Long-Lasting Impact of Maternal Immune Activation and Interaction With a Second Immune Challenge on Pig Behavior - Rymut, Haley E.; Bolt, Courtni R.; Caputo, Megan P.; Houser, Alexandra K.; Antonson, Adrienne M.; Zimmerman, Jalisa D.; Villamil, Maria B.; Southey, Bruce R.; Rund, Laurie A.; Johnson, Rodney W.; Rodriguez-Zas, Sandra L. (Frontiers in Veterinary Science, 2020)
The combined effects on pig behavior of maternal immune challenge during gestation followed by a second immune challenge later in life have not been studied. Porcine reproductive and respiratory syndrome virus (PRRSV) infection during gestation can elicit maternal immune activation (MIA) yet the interactions with the offspring response to a second immune challenge after birth remains unexplored. Knowledge on the response to viral challenges in rodents has been gained through the use of the viral mimetic polyinosinic-polycytidylic acid (Poly(I:C)), yet the effects of this immune stimulant on pig behavior have not been assessed. This study advances the understanding of the combined effect of MIA and a second immune challenge later in life on female and male pig behavior. Three complementary experiments enabled the development of an effective Poly(I:C) challenge in pigs, and testing the interaction between PRRSV-elicited MIA, Poly(I:C) challenge at 60 days of age, and sex on behaviors. Individual-level observations on sickness, locomotor, and social behaviors were measured 1-3 hours after Poly(I:C) challenge. Vomiting, panting, lethargy, walking, laying, playing, and touching behaviors were analyzed using generalized linear mixed effect models. Results indicated that a Poly(I:C) dose of 1 mg/kg within 1 hour after injection increased the incidence of laying and sickness behavior. The Poly(I:C) challenge decreased the incidence of locomotor behaviors and activity levels. Pigs exposed to MIA had lower rates of social behaviors such as playing. The combined effect of PRRSV-elicited MIA and Poly(I:C) immune challenge further sensitized the pigs to behavior disruption across sexes including changes in sternal and lateral laying, walking, lethargy, and touching incidence. Notably, the effects of Poly(I:C) immune challenge alone on behaviors tended to be more extreme in males, whereas the effects of Poly(I:C) following MIA tended to be more extreme in females. Our findings demonstrate that MIA and Poly(I:C) affected behaviors, and the viral mimetic effects shortly after injection can offer insights into the prolonged effect of postnatal viral infections on feeding, social interactions and health status. Management practices that reduce the likelihood of gestational diseases and accommodate for behavioral disruptions in the offspring can minimize the impact of MIA.